Factors Affecting the Performance of State Civil Servants at the Education and Culture Services of Kaur District - Yosi Novita Sari; Ida Ayu Made Ermetha Gyatri; Nenden Restu Hidayah (Penerbit Jurnal Indonesia, 2021)
The method used in collecting data for this research is a questionnaire. The data analysis method in this research is quantitative, and the sample in this study is 140 customers. Based on the results of this study concluded that: The regression equation obtained from the research results are as follows: Y = 6.263 + 0.588X1 + 0.574 X2 + e. The value of the termination coefficient R2 = 0.792. This value means that independent and dependent, contributed 79.2% in influencing the dependent variable while the rest was influenced by other variables not examined. The t test is used to determine the effect of each independent variable on the dependent variable by looking at the tsig value compared to 0.05. From the table above, the tsig value of X1 is 0.001, and X2 is 0.005. From the tsig value, it is found that the X1 variable has an effect on Y and the X2 variable has an effect on Y, 4). Fsig value 0.002 < 0.05, so it can be concluded that the variables (X1) and (X2) have an effect on the variable (Y) or together have a simultaneous effect